Efficacy of percutaneous cement discoplasty combined with PVP for the treatment of stage III Kümmell disease with an adjacent disc vacuum sign - Liu, Liehua; Li, Pei; Luo, Lei; Zhao, Chen; Zhang, Huilin; Liu, Deqiang; Zhou, Qiang (Frontiers in Surgery, 2025)
ObjectiveTo observe the efficacy of percutaneous cement discoplasty (PCD) combined with PVP for the treatment of stage III Kümmell disease (KD).MethodsA total of 33 patients with stage III KD who underwent surgical treatment were divided into the PCD + PVP (PP) group (n = 20) and the internal fixation and fusion (IFF) group (n = 13). The observation indices included demographic characteristics, perioperative information, and clinical and imaging indicators, including the visual analog score (VAS), Oswestry disability index (ODI), Cobb angle, and height ratio of the injured vertebra and its adjacent intervertebral disc (Hv+d, RHv+d).ResultsThe operation time, blood loss, duration of bedrest, length of stay and cost of hospitalization were significantly lower in the PP group than in the IFF group (P < 0.001). There were no significant differences in the VAS score or ODI between the two groups before the operation, after the operation or at the last follow-up (P > 0.05). The RHv + d in the IFF group was significantly higher than that in the PP group after surgery and at the last follow-up (P < 0.05). The Cobb angle in the IFF group was significantly smaller after the operation than before the operation (P = 0.007). The incidence of complications in the PP group was lower than that in the IFF group (P = 0.018).ConclusionsPCD combined with PVP for the treatment of stage III KD with an adjacent disc vacuum sign is effective and may be the next best thing to IFF, especially for elderly patients with complex underlying diseases and great surgical risks.